Acute stroke patterns in patients with internal carotid artery disease: a diffusion-weighted magnetic resonance imaging study - Szabo, Kristina; Kern, Rolf; Gass, Achim; Hirsch, Jochen; Hennerici, Michael G. (Stroke, 2001)
Background and Purpose: Diffusion-weighted (DW) MRI is a sensitive method that facilitates early stroke pattern identification. There are limited data about the influence of stenosis grade on the development of particular stroke patterns in internal carotid artery (ICA) disease. We therefore investigated the lesion patterns on DW MRI in acute stroke patients with ICA disease.Methods—DW MRI was analyzed in 102 consecutive acute stroke patients with different degrees of ipsilateral ICA disease. Patients were assigned to 1 of 5 observed lesion patterns: (1) territorial ischemia, (2) subcortical ischemia without or (3) with embolus fragmentation, (4) disseminated lesions in distal cortical regions, and (5) multiple lesions in hemodynamic risk zones. In addition, perfusion-weighted (PW) MRI and MR angiography information was included in the assessment.Results—All patterns were observed in the different stages of ICA disease. Half of the patients with high-grade or subtotal stenosis had lesions in hemodynamic risk zones. Territorial stroke occurred in 47.6% of patients with ICA occlusion. Statistical analysis showed a significant relationship between the degree of stenosis and the observed stroke pattern (P=0.001). In 77.8% of patients exhibiting high-grade ICA stenosis, subtotal stenosis, or occlusion, the perfusion lesion was larger than the diffusion lesion (PW/DW mismatch).Conclusions—Although in the individual patient any of the infarct patterns may occur, in statistical terms the incidence of a particular stroke pattern is clearly dependent on the degree of stenosis.
Gesehen am 31.03.2021